When time does not heal all wounds: three decades’ experience of immigrants living in Sweden - Ferid Krupić; Monika Moravcova; Emina Dervišević; Svemir Čustović; Kemal Grbić; Parvaneh Lindström (Medicinski glasnik, 2024)
Aim: To investigate how immigrants from the Balkan region experienced their current life situation after living in Sweden for 30 years or more. Methods: The study was designed as a qualitative study using data from interviews with informants from five Balkan countries. The inclusion criteria were informants who were immigrants to Sweden and had lived in Sweden for more than 30 years. Five groups comprising sixteen informants were invited to participate in the study, and they all agreed. Results: The analysis of the interviews resulted in three main categories: “from someone to no one”, “labour market”, and “discrimination”. All the informants reported that having an education and life experience was worth-less, having a life but having to start over, re-educating, applying for many jobs but often not being answered, and finally getting a job for which every in-formant was educated but being humiliated every day and treated separately as well as being discriminated against. Conclusion: Coming to Sweden with all their problems, having an education and work experience that was equal to zero in Sweden, studying Swedish and re-reading/repeating all their education, looking for a job and not receiving answers to applications, and finally getting a job but being treated differently and discriminated against on a daily basis was experienced by all the in-formants as terrible. Even though there are enough similar studies in Sweden, it is always good to write more to help prospective immigrants and prospective employers in Sweden.
Keywords: immigrants; experiences; discrimination; qualitative; Sweden